Ortner’s Syndrome in Rheumatic Mitral Stenosis: A Case Report - Hussain, Asraf; Bhardwaz, Prashant Shivam; Ghimire, Moniska (Journal of National Heart and Lung Society Nepal, 2024)
BACKGROUNDOrtner’s syndrome (OS), alternatively known as cardio vocal syndrome, is a disorder characterized by left recurrent laryngeal nerve palsy as a result of underlying cardiopulmonary disease. One of the most important causes is an enlarged left atrium as in case of mitral stenosis. Rheumatic heart disease is still the commonest cause of significant valvular heart disease in the developing world. Lack of health infrastructure leads to late diagnosis of rheumatic heart disease. Most of the patients present with very advanced stages of valvular heart disease. CASE PRESENTATIONWe present here a case of a 48-year-old female with rheumatic mitral stenosis. Due to late diagnosis she had developed a rare complication in the form of Ortner’s Syndrome. CONCLUSIONSFocused screening for acute rheumatic fever and rheumatic heart disease among school-going children along with adequate secondary prophylaxis would be of great help in early diagnosis and management of valvular and extravalvular complications of rheumatic heart disease including Ortner’s syndrome.